Russian Scholarly Publications in Anglophone Academic Discourse: The Clash of Tyrannosaurs - Irina B. Korotkina (National Research Mordova State University, 2018)
The predominance of English in scholarly publications, recently defined as linguistic imperialism, is no longer considered a threat for multilingual scholars, but a shared linguistic code essential in creating and communicating knowledge. A more significant threat for Russian scholars is the Russian tradition of scholarly writing, which originates from the Soviet period and affects the quality of their national and international publications, especially in humanities and social sciences. The solution is seen in developing writing for academic and research publication purposes in both English and Russian within the umbrella framework of academic literacy. The pioneering role in overcoming the resistance of the deeply rooted tradition and promoting academic writing as a discipline, Russian university writing centers, recently united into the National Consortium, play the central role. Explicit bilingual programmes are especially effective in countries with low level of English, and can be applied to various cultural contexts. They can be further developed into trilingual programmes in post-Soviet states, who experience similar difficulties and for whom Russian remains the lingua franca of academic communication.